Publiczny a prywatny. Próby demonopolizacji płatnika trzeciej strony w Polsce (aspekt polityczny i ekonomiczny) - Bromber, Piotr (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2013)
This paper is an attempt at an assessment of the discussion and steps taken in order to demonopolize a third party payer in Poland, in particular as regards a patient’s right to choose the payer. For the purpose of this analysis it is assumed that a patient should have the right to choose a third party payer. It is also assumed, however, that a patient’s attitude transforms from being demanding into the attitude of an active and aware patient caring for his own health. The author indicates that the manner of operation of a third party payer should be a result of the system of health protection, its scope and objectives. Finally, the concept of introducing competition is considered, but only in the case of voluntary health insurance policies and a single but decentralized payer in the public health insurance.
Public versus private. Attempts at the demonopolization of a third party payer in Poland (political and economic aspects)